2022
DOI: 10.1371/journal.pone.0273019
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of relative age effects in Luxembourg’s male and female youth football

Abstract: The relative age effect (RAE) is a well-established phenomenon in football. However, while the majority of previous studies focussed on established football nations, it remains unclear if the constraint of a limited population of soccer players in smaller countries associated with less strict selection procedures may reduce the risk of RAE. This study aims to investigate the RAE in Luxembourg that follows an ‘open-door’ selection policy in youth football due to the limited pool of players. Birthdates from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…While our study did not reveal a relative age effect among top-ranked players in the Ballon d’Or, it is noteworthy that in badminton, lower categories demonstrated a significant RAE between 2014 and 2018, particularly in players winning medals at European championships [ 36 ]. This finding, despite the different contexts and age groups analyzed in our study (senior category), aligns with the established trend that RAE tends to be more consistent in lower categories [ 37 ] both in male sports [ 3 , 6 , 11 , 14 , 38 ] and in female sport [ 6 , 8 ], although in the female category, this trend is less consistent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While our study did not reveal a relative age effect among top-ranked players in the Ballon d’Or, it is noteworthy that in badminton, lower categories demonstrated a significant RAE between 2014 and 2018, particularly in players winning medals at European championships [ 36 ]. This finding, despite the different contexts and age groups analyzed in our study (senior category), aligns with the established trend that RAE tends to be more consistent in lower categories [ 37 ] both in male sports [ 3 , 6 , 11 , 14 , 38 ] and in female sport [ 6 , 8 ], although in the female category, this trend is less consistent.…”
Section: Discussionsupporting
confidence: 89%
“…In sports, the cutoff date is commonly set as the 1st of January in most competitions, giving players born in the first months of the year a sporting advantage (explained by the maturational profile associated with a late maturation of athletes born in the last months of the year) [ 3 ]. In most countries, the cutoff date for youth sports is the 1st of January [ 4 ], and in football, the Fédération Internationale de Football Association (FIFA) youth tournaments have also used this cutoff date to establish age groups since 1997 [ 5 , 6 ]. In professional football the cutoff date can vary between countries; for example, England uses August 1st [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, when organizing junior tournaments, the CTA should mitigate the negative impact of the RAE by reforming the grouping designations of junior tournaments and the cut-off dates for rotating competition groupings. Finally, as Simon et al [ 68 ] suggested, coaches need to retain all players to some extent and avoid selecting only the most athletically accomplished so that late-born athletes can have the same opportunities to train and compete as early-born athletes. We suggest that Chinese tennis coaches, when training and organizing their teams, should not limit themselves to the performance of junior athletes in terms of physical morphology indicators and so on, but should give full consideration to athletes born in different years and times of the year.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis was completed using the Jamovi Project. Chi-square goodness of fit test was used to compare the birth distribution of academy players to the national population distribution for Japan (observed vs expected), with Cramer's V: small (0.06 ≥), medium (0.17 ≥), and large (0.29 ≥) to analyse effect sizes [5,21]. Correspondingly, the odd ratio test (OR) was used to compare the odds of players in Q1, Q2, and Q3 with the odds of a player in Q4 to interpret the differences across quarters [13,22].…”
Section: Discussionmentioning
confidence: 99%